User-based innovation in services - Sundbo, Jon (Edward Elgar Publishing Ltd. CheltenhamGB, 2012)
Offers a broad view of innovation, which when accumulated may function as a catalyst which leads to significant changes in service practice, be it in customer services, public services or industrial services.